Improving the robustness and efficiency of cell sheet protocol for breast cancer induction in animal model: A Geltrex plus Gelatin approach - Alaa T. Alshareeda; Nada Albarakati; Yasser Alshawakir; Ayidah Alghuwainem; Batla S. Al-Sowayan; Abdul Latif Khan; Abdullah Almubarak; Sarah Al-Maiman; Ahood Al Sayed; Nur Khatijah Mohd Zin; Amal S. Alhamid (PLoS ONE, 2025)
Background Breast cancer remains a global health challenge, necessitating improved preclinical models that better mimic the complexity of the disease. The cell sheet technique holds promise in creating three-dimensional tissue constructs resembling breast cancer tissue. However, maintaining cell sheet integrity during transplantation poses challenges, particularly with low junction cells. This study aims to establish a modified protocol utilizing Geltrex™ and Gelatin to fabricate cell sheets from MDA-MB-231 cells and evaluate their tumorigenic potential in vivo. Method We developed a novel protocol for fabricating cell sheets from MDA-MB-231 cells using Geltrex™ and Gelatin. This construct was then used to induce breast cancer in vivo. The novel protocol was compared to the conventional cell injection method by monitoring tumor progression in vivo. Results The novel protocol enhanced cell sheet transplant efficiency by providing scaffold support and temporary adhesion. It successfully induced breast cancer in vivo and facilitated metastasis, closely mimicking the progression of human breast cancer. Conclusion This study highlights the potential of Geltrex™ and Gelatin as carriers for poor junction cell sheets. This original research study introduces a methodological advance in cell sheet fabrication, combining preclinical validation with technical innovation to address challenges in modeling triple-negative breast cancer (TNBC). By offering a more accurate in vivo representation of tumor development, this protocol enhances our understanding of breast cancer biology. The practical implications are promising, as this research can lead to more effective methods for generating in vivo models and tissue-engineered constructs for cancer research and regenerative medicine.